Gambaran Pengetahuan Remaja Tentang Kesehatan Reproduksi di SMP Negeri 3 Selemadeg Timur Tahun 2019 - Cokorda Istri Mita Pemayun; MADE DEWI SARIYANI; Lakitha Ning Utami (STIKES ADVAITA MEDIKA TABANAN, 2019)
Adolescence is a period of transition from children to adults who marked change in the physical, emotional and psychological. Reproductive health knowledge is important for adolescents to improve health behaviors, to avoid free sex, and decrease in the number of infectious illness sex. The purpose of this study was to overview knowledge of reproductive health among adolescents. This study was a descriptive design. This research was conducted on May 23, 2019 in East Selemadeg Middle School 3. The sample was selected using purposive sampling. The sample used is 50 people. Instrument used to measure knowledge using a questionnaire. Data analysis using the chi-square test. The results of the study of 50 students distributed into sub-topics on reproductive health showed that 29 people (58%) knew the notion of reproductive health; 26 people (52%) knew the right to reproductive health; 42 people (84%) did not know the growth and development of adolescence; 35 people (70%) did not know the reproductive function; 26 people (52%) knew the signs of reproductive organ maturity and as many as 42 people (84%) did not know of sexually transmitted diseases. The data showed that the teenager Yang memilki Still Few Good knowledge that Need No Further Research The interventions to improve the knowledge of the respondent review.